The Psychology of Mindfulness for Pre-Service Teachers Preparation Program - Kusumawardani, Irene Nany; Ghozali, Muhammad Afifuddin; Unsiah, Frida; Degeng, Putu Dian Danayanti; Isnaini, Moh. Hasbullah (OJS Universitas Muhammadiyah Gresik, 2025)
The benefits of mindfulness in adults have been widely researched, and its positive impact on psychology and teacher performance has become a major focus in the field of education. These benefits include stress regulation and reduction, increased compassion, and improved teaching effectiveness. Many studies have highlighted the positive relationship between mindfulness traits and teaching readiness. This study specifically examines the role of prospective teachers' mindfulness traits in their readiness to teach. The theoretical model proposed by Manasia et al. (2019), which includes four key dimensions of teaching, was used to measure the teaching readiness of prospective teachers in three academic programs at the Department of Language Education at a leading state university in Malang, East Java, Indonesia. The Five Facet Mindfulness Questionnaire (FFMQ) was employed to measure the mindfulness traits of students as future teachers. The study found that mindfulness traits were able to predict higher teaching readiness in participants. These findings also form the basis for a community service activity, which involves providing mindfulness psychology training during teaching preparation orientation for students as prospective teachers.